In situ thermal characterization of rice straw envelope of an outdoor test room. (January 2021) - Sabapathy, Karthik A.; Gedupudi, Sateesh
Abstract: The after-effects of human-induced climate change pose complex engineering challenges to the building sector. One of the ways of reducing the carbon footprint of buildings is the use of bio-based construction materials with capacity to passively manage the hygrothermal performance of buildings. Research during the recent years has led to the emergence of straw as a potential candidate. In the present study, with the aim of in situ data extraction from a straw envelope and the subsequent thermal characterization of straw, a test room of 10 cm thick raw rice straw envelope was designed and built. The effective thermal and moisture diffusivities of the straw envelope based on the collected temperature and relative humidity data were evaluated. Four commonly used models were selected to predict the outside heat transfer coefficient for the rough surface of the straw envelope. A comparison between the surface temperatures from the experiment and the 1-D transient numerical studies employing the model-derived outside heat transfer coefficients and sol-air temperatures pointed to the DOE-2 model being the best suited with 92% of the predicted surface temperatures within ± 15% of the experiment values. A similar comparison study was employed to verify the ranges of inside heat transfer coefficient. The study provides a framework for the determination of the thermal transmittance of straw based walls and helps in the optimum thermal design of a straw envelope. Highlights: A test room with 10 cm thick envelope made of rice straw cells was designed and built. Thermal diffusivity and moisture diffusivity based on in situ data were estimated. Four models for calculating outside convection heat transfer coefficient are compared. The study recommends a range of thermal transmittance values for straw envelopes.